The Effectiveness of Thermotherapy against Cassava Mosaic Disease: A Field Evaluation in Central African Republic - Zinga, Innocent; Chiroleu , Frédéric; Kamba , Emmanuel; Giraud-Carrier , Charlotte; Harimalala , Mireille; Komba , Ephrem Kosh; Yandia , Simplice; Semballa , Silla; Reynaud , Bernard; Dintinger , Jacques; Lefeuvre , Pierre; Lett , Jean-Michel (Emerging Issues in Agricultural Sciences Vol. 9, 2023)
The effectiveness of thermotherapy in treating CMD in the field and under etiological settings in the Central African Republic is examined in this paper's findings. Finding low-cost, easily implemented management strategies that may be made popular in rural regions received special consideration. Cassava (Manihot esculenta Crantz) is one of the most important root staple crops. An estimated 30% of Zambians, over 4 million people, consume cassava as part of their daily diet. Cassava is mostly grown by subsistence farmers on fields of less than 1 ha. Cultivation of cassava is hampered by several biotic constraints, of which cassava mosaic disease (CMD) is currently the most important factor limiting cassava production. The most significant biotic limitation, cassava mosaic disease (CMD), significantly lowers production. According to certain research, thermotherapy can be used to manage CMD in Africa. Diseased cassava cuttings were treated in a heated water bath at temperatures ranging from 43°C to 51°C for 30 min before being grown for 12 months in the field. Temperatures from 43°C to 49°C were found to have no deleterious effect on either the survival of cuttings or on plant regeneration. One month after planting (MAP), up to 40% of the cuttings treated at 47°C to 49°C had regenerated a plant with no CMD symptoms compared to 7% of untreated cuttings. Between two and five MAP, cassava cuttings treated at 49°C produced plants with a significantly lower incidence of CMD than plants produced from untreated cuttings. All plants grown from treated cuttings developed significantly less severe CMD symptoms than untreated cuttings between 8 and 12 months after planting. The highest tuberous root yield was obtained with diseased cuttings treated at 49°C (4.7 kg/plant), equivalent to the yield from untreated symptomless cuttings (4.6 kg/plant). Our data clearly demonstrate the value of thermotherapy to maintain a high level of production using local cultivars under severe CMD epidemic conditions.